PHYSICAL EDUCATION IN THE STATE OF PARANÁ A DISCUSSION PEDAGOGYCAL (Fiep Bulletin - online, 2016)
This paper presents a reflection on the current understanding of the Ministry of Education of Paraná about Physical Education, officially demonstrated through events such as curriculum reform and enhancement of training hours, aiming to prepare teams for competitions. The proposal was to analyze the understanding of physical education in the face of cultural approaches and corporeality, permeated by the analysis of national curriculum guidelines, national curriculum guidelines and state curriculum guidelines. This makes it possible to realize by the Department of Education of Paraná defend a vision of esportivação Physical Education classes, denying the methodological discussion that converges to the body culture. It was evident that only from this approach is that we have a Physical Education significance within the school and in the lives of students, providing them with conditions to have a full training and able to act consciously and critically in society that insert.
Keywords: Physical Education; esportivação; culture; body